2020
DOI: 10.1002/ecs2.3137
|View full text |Cite
|
Sign up to set email alerts
|

Comparing models using air and water temperature to forecast an aquatic invasive species response to climate change

Abstract: Understanding invasive species spread and projecting how distributions will respond to climate change is a central task for ecologists. Typically, current and projected air temperatures are used to forecast future distributions of invasive species based on climate matching in an ecological niche modeling approach. While this approach was originally developed for terrestrial species, it has also been widely applied to aquatic species even though aquatic species do not experience air temperatures directly. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…In response to the increasing demand for T w data which nowadays are included in major environmental studies, especially climatic changes, continuous knowledge of its variation has becoming a priority for a large number of countries worldwide and has been included in their monitoring and management programmes (Tavares et al, 2020). For example, it was demonstrated that T w can be used as an important predictor for aquatic invasive species (Walsh et al, 2020), and it should be taken into account that T w should be considered in all studies and knowledge related to the habitat of river ecosystems (Morid et al, 2020). Although T w is one of the simplest measures of water quality, available information is still limited in terms of temporal frequency and representativeness (Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In response to the increasing demand for T w data which nowadays are included in major environmental studies, especially climatic changes, continuous knowledge of its variation has becoming a priority for a large number of countries worldwide and has been included in their monitoring and management programmes (Tavares et al, 2020). For example, it was demonstrated that T w can be used as an important predictor for aquatic invasive species (Walsh et al, 2020), and it should be taken into account that T w should be considered in all studies and knowledge related to the habitat of river ecosystems (Morid et al, 2020). Although T w is one of the simplest measures of water quality, available information is still limited in terms of temporal frequency and representativeness (Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond changes in habitat, losses of winter ice are yielding uncertain outcomes for ice fishing (Sharma et al, 2020), historically a period of high effort in Wisconsin (Feiner et al, 2020b). Climate change also threatens to exacerbate the risks of other stressors like heat‐induced fish kills (Till et al, 2019), range expansions of invasive species (Walsh et al, 2020), and more frequent and extreme floods (Dauwalter & Mitro, 2019; Gudmundsson et al, 2021), which can substantially threaten valuable native fish communities.…”
Section: Introductionmentioning
confidence: 99%
“…Temperatures vary across time and space and can substantially differ between the air, water, and soils. Although air temperatures have been extensively measured using global networks or satellites, there has been less attention towards soil and water temperatures [ 3 , 6 , 9 , 10 ]. This is unfortunate because many biological and biogeochemical processes rely on proximate temperatures in soil and water that can differ widely from those in the air [ 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although air temperatures have been extensively measured using global networks or satellites, there has been less attention towards soil and water temperatures [ 3 , 6 , 9 , 10 ]. This is unfortunate because many biological and biogeochemical processes rely on proximate temperatures in soil and water that can differ widely from those in the air [ 10 , 11 , 12 , 13 , 14 , 15 ]. In soils, temperatures can be difficult to predict from those in the air because of their dependence on radiation load, surface energy budget partitioning, soil depth, and soil thermal properties that vary with soil texture and moisture content [ 12 , 13 , 14 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%